PEMANFAATAN WORTEL (Daucus carota L.) DALAM MENINGKATKAN MUTU NUGGET TEMPE - ADI WIBOWO '; FAIZAH HAMZAH '; VONNY SETIARIES JOHAN (Universitas Riau, 2014)
The purpose of this study was to obtain the best tempeh nugget with the addition of carrot in term of nutrientcontent, fiber level and organoleptic test. This study used a Complete Randomized Design (CRD) with fourtreatments and four replications treatment. The treatments were TW1 (90% tempeh : 10% carrot), TW2 (80%tempeh : 20% carrot), TW3 (70% tempeh : 30% carrot), TW4 (60% tempeh : 40% carrot). Data obtained weretreated by the analysis of variance followed by Duncan New Multiple Range Test (DNMRT) at the level of 5%.The results show that the ratio of tempeh and carrot in each treatment significantly affected to the moisture,fiber, ash and protein content, taste hedonic, texture but did not significantly affected to color, flavor andoverall assessment. The best treatments in this research was TW4, with moisture content of 52,73%; proteincontent 13,37% that meet the quality standard of chicken nugget (SNI 01-6683-2002). The ash content1,53% and fiber content 3,12% was quite higher than those of standard.Key words: Nugget, Tempeh, carrot, fiber